How providers influence the implementation of provider-initiated HIV testing and counseling in Botswana: a qualitative study. (December 2015) - Ahmed, Shahira; Bärnighausen, Till; Daniels, Norman; Marlink, Richard; Roberts, Marc
Abstract Background Understanding the motivations and perspectives of providers in following guidance and evidence-based policies can contribute to the evidence on how to better implement and deliver care, particularly in resource-constrained settings. This study explored how providers' attitudes and behaviors influenced the implementation of an intervention, provider-initiated HIV testing and counseling, in primary health care settings in Botswana. Methods Using a grounded-theory approach, we purposively selected and interviewed 45 providers in 15 facilities in 3 districts and inductively analyzed data for themes and patterns. Results We found that nurses across facilities and districts were largely resistant to offering and delivering provider-initiated testing and counseling for HIV (PITC) for three reasons: (1) they felt they were overworked and had no time, (2) they felt it was not their job, and (3) they were afraid to counsel patients, particularly fearing a positive HIV test. These factors were largely related to health system constraints that affected the capacity of providers to do their job. An important underlying themes emerged: nurses and lay counselors were unsatisfied with pay and career prospects, which made them unmotivated to work in general. Variations were seen by urban and rural areas: nurses in urban areas felt generally overworked and PITC was seen as contributing to the workload. While nurses in rural areas did not feel overworked, they felt that PITC was not their job and they were unmotivated because of general unhappiness with their rural posts. Conclusions The attitudes and behaviors of providers and barriers they faced played a critical role in whether and how PITC was being implemented in Botswana. Provider factors should be considered in the improvement of existing PITC programs and design of new ones. Addressing constraints faced by providers can do more to improve supply of human resources than merely recruiting more providers.